2015
DOI: 10.7314/apjcp.2015.16.10.4435
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment the Relationship between p21 rs1059234 Polymorphism and Cancer Risk

Abstract: p21 is a cyclin-dependent kinase inhibitor, which can arrest cell proliferation and serve as a tumor suppressor. Though many studies were published to assess the relationship between p21 rs1059234 polymorphism and various cancer risks, there was no definite conclusion on this association. To derive a more precise quantitative assessment of the relationship, a large scale meta-analysis of 5,963 cases and 8,405 controls from 16 eligible published case-control studies was performed. Our analysis suggested that rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Inconsistent with our observations, the case and control groups were not significantly different [17]. The association between P21 polymorphisms and susceptibility to uterine leiomyoma [14], late-onset Alzheimer’s disease [37], and cancer [38] has been investigated in the literature; however, the effects of P21 polymorphisms on diseases are controversial. In addition, we found that level of relative placental mRNA expression in TP53 gene was 5.6 times higher in the PE group ( P < 0.0001), however, TP53 mRNA expression showed no significant difference between rs1042522 genotypes.…”
Section: Discussionsupporting
confidence: 72%
“…Inconsistent with our observations, the case and control groups were not significantly different [17]. The association between P21 polymorphisms and susceptibility to uterine leiomyoma [14], late-onset Alzheimer’s disease [37], and cancer [38] has been investigated in the literature; however, the effects of P21 polymorphisms on diseases are controversial. In addition, we found that level of relative placental mRNA expression in TP53 gene was 5.6 times higher in the PE group ( P < 0.0001), however, TP53 mRNA expression showed no significant difference between rs1042522 genotypes.…”
Section: Discussionsupporting
confidence: 72%
“…For example Li [38] observed no association between C70T polymorphism and cancer. Recently, in a metaanalysis conducted by Huang on 5963 cases and 8405 controls from 16 published case-control studies, no significant correlation was found between C70T polymorphism and cancer risk neither in dominant model [(T/T + C/T) vs. C/C)] nor in recessive model [T/T vs. (C/C + CT)] [39].…”
Section: Discussionmentioning
confidence: 99%